2019
DOI: 10.1016/j.nmni.2019.100560
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and antimicrobial activity of lactic acid bacteria from raw camel milk

Abstract: Consumer demand for natural pathogen-control agents for substitution of synthetic food preservatives and traditional antibiotics is increasing. This study aimed to reveal the distribution of lactic acid bacteria (LAB) in raw camel milk and to characterize their antimicrobial traits. The genetic identification by 16S rRNA sequencing of 58 LAB isolates showed the predominance of Enterococcus (24.2%), Lactococcus (22.4%) and Pediococcus (20.7%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…revealed strong antibacterial activity than isolates with RFLP pattern I that consist of Enterococcus subsp. Similar results were reported on antibacterial activity of LAB isolated from raw camel milk (Rahmeh et al., 2019), Genestoso cheese (González et al., 2007) and Brazilian artisanal cheeses (Margalho et al., 2020). Organic acids production, as the main antibacterial agents, by LAB is mainly a genus‐specific phenomenon and partially specie‐specific.…”
Section: Discussionsupporting
confidence: 86%
“…revealed strong antibacterial activity than isolates with RFLP pattern I that consist of Enterococcus subsp. Similar results were reported on antibacterial activity of LAB isolated from raw camel milk (Rahmeh et al., 2019), Genestoso cheese (González et al., 2007) and Brazilian artisanal cheeses (Margalho et al., 2020). Organic acids production, as the main antibacterial agents, by LAB is mainly a genus‐specific phenomenon and partially specie‐specific.…”
Section: Discussionsupporting
confidence: 86%
“…The Lactobacillus acidophilus AA105 strain from camel milk is a potent inhibitor of Salmonella paratyphi, Shigella spp., and pathogenic E. coli (Abo-Amer, 2013), and L. brevis CM22 demonstrated inhibitory effects against Listeria spp. (Rahmeh et al, 2019). Interestingly, a recent report of Elbanna et al (2018) showed that L. paracasei Pro4 and L. rhamnosus Pro7 isolated from fermented camel milk modulate the intestinal immunity after oral administration in mice by improving the expression of Toll-like receptor (TLR)-2, interferon (IFN)-γ, and secretory immunoglobulin A (IgA) indicating that LAB isolated from the milk of camelids can be beneficial modulators of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Fermented camel milk, named shubat, is also known for its medicinal and dietary properties [2] . LAB is the dominant population in raw and fermented milk; they produce various antimicrobials such as organic acids and hydrogen peroxide, antifungal peptides and bacteriocins and play a crucial role in food fermentation processes [3] . The isolation and characterization of resident LAB in raw and fermented camel milk are essential for further development starters of functional camel-milk-derived products.…”
Section: Datamentioning
confidence: 99%